Efektivitas Pelatihan Keselamatan Kerja di Konstruksi Dan Peran Manajemen dalam Meningkatkan Kepatuhan K3 ; Literatur Review - Yani, Akhmad (Jurnal Ilmiah Ekonomi Manajemen & Bisnis, 2025)
This study aims to evaluate the effectiveness of safety training programs in the construction sector and the role of management in enhancing compliance with Occupational Health and Safety (OHS) standards through a literature review. The research employs a literature study method, gathering data from 20 articles indexed in Sinta and Scopus between 2018 and 2023. Conducted over two months (June and July 2024), the study identifies the most effective training methods for improving OHS compliance. It also highlights the managerial role in ensuring that safety training is well adopted and implemented by workers on-site. The findings reveal that from 2018 to 2023, the implementation of OHS across various sectors has shown significant progress, particularly with the adoption of advanced technologies like Virtual Reality (VR) and the Internet of Things (IoT). However, gaps in understanding and applying OHS, especially in SMEs and construction, persist, with a need for increased awareness and comprehension. A more proactive managerial role and the integration of smart technologies are crucial for enhancing the effectiveness of OHS training and worker safety. Future research should explore the broader application of VR and IoT in various sectors and assess the long-term effectiveness of OHS training programs supported by these technologies. Further studies are needed to address the challenges in implementing OHS in SMEs and construction to achieve higher safety standards